2022
DOI: 10.1136/openhrt-2021-001808
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and haemodynamic profiles of pulmonary hypertension in cardiac amyloidosis

Abstract: ObjectivesWhile cardiac amyloidosis (CA) classically involves the left ventricle (LV), less is known about its impact on the right ventricle (RV) and pulmonary vasculature. We performed a retrospective analysis to identify the prevalence and types of pulmonary hypertension (PH) profiles in CA and to determine haemodynamic and cardiovascular magnetic resonance (CMR) predictors of major adverse cardiovascular events (MACE).MethodsPatients with CA who underwent CMR and right heart catheterisation (RHC) within 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…However, it is difficult to differentiate between these two pathophysiological mechanisms. 21 Additionally, secondary hepatic lesions occur from monoclonal light chain or associated fragment deposits and this may best be reflected by ALP levels. 22 This concurs with recent Chinese studies that found total bilirubin was independently associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to differentiate between these two pathophysiological mechanisms. 21 Additionally, secondary hepatic lesions occur from monoclonal light chain or associated fragment deposits and this may best be reflected by ALP levels. 22 This concurs with recent Chinese studies that found total bilirubin was independently associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Also, altered hepatic function in amyloidosis is multifactorial and complex but is principally caused by cardiac failure and hepatic amyloid infiltration. However, it is difficult to differentiate between these two pathophysiological mechanisms 21 . Additionally, secondary hepatic lesions occur from monoclonal light chain or associated fragment deposits and this may best be reflected by ALP levels 22 …”
Section: Discussionmentioning
confidence: 99%
“…Only a limited amount of studies evaluated the relation between hemodynamics and clinical outcome in CA, showing that RAP was independently associated with clinical outcome. 6,7 No studies have previously analyzed if the classic hemodynamic cutoffs, heavily embedded in clinical practice, convey risk information. We specifically looked at the prognostic impact of CI <2.2 L/min per m² and PCWP >18 mm Hg, a cutoff that was validated in 1976 in patients with an acute myocardial infarction in the seminal paper of Forrester and Diamond and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have reported on the cardiac hemodynamic profiles in CA and the limited data show conflicting results as to whether ATTR-CA and AL-CA are affected by a same degree of hemodynamic alteration. [4][5][6][7] There is a need to understand the prognostic value of hemodynamic variables and pulmonary hypertension (PH) in CA.…”
mentioning
confidence: 99%
“…The cardinal symptom is exertional dyspnoea 5,6 . Isolated post‐capillary PH and combined pre‐ and post‐capillary PH are prevalent in these patients 7,8 . and associated with adverse outcomes 9–11 .…”
Section: Introductionmentioning
confidence: 99%